GLS to Develop Reading Interest of Junior High School Students: An Ethnographic Review - Zoromi, Marta Rita; Listyani, Listyani; Mawardi, Mawardi (LPPM Universitas PGRI Sumatera Barat, 2023)
This study aims to explore the implementation of the School Literacy Movement (GLS) program at SMP Negeri 4 Namohalu Esiwa through an ethnographic approach. It examines the perceptions of teachers, students, and parents regarding the program, literacy practices within the school, socio-cultural barriers, and school culture factors that support students' reading interest. Data were collected through observations, in-depth interviews, and document analysis. The findings reveal that the GLS program at SMP Negeri 4 Namohalu Esiwa has not yet effectively improved students' reading interest due to limited library facilities, insufficient access to relevant reading materials, and low parental involvement in supporting students' literacy development. Furthermore, the local culture, which emphasizes oral traditions over written literacy, poses a significant challenge. Nevertheless, teacher support and literacy activities such as reading corners and a 15-minute pre-class reading period demonstrate potential for further development. This study recommends enhancing literacy facilities, providing teacher training, fostering collaboration among schools, parents, and communities, and integrating local cultural elements into the GLS program. These steps are expected to foster a sustainable literacy culture and significantly improve students' reading interest.